PEMBENTUKAN KEJUJURAN SOSIAL SANTRI MELALUI INTERNALISASI NILAI-NILAI TA’LIM AL-MUTA’ALLIM DI ERA GLOBALISASI - Ahmad Yusron Hafizi; Muhammad Asadullah Akbar; Muhammad Jaelani (Maharah: Journal of Islamic Education Teaching and Learning, 2025)
The declining quality of students’ respect and manners toward teachers in various educational institutions, including Islamic boarding schools (pesantren), raises concerns over the erosion of moral values in Islamic education. This study aims to analyze how the teaching of Ta’lim al-Muta’allim shapes students’ social honesty at Pondok Pesantren Miftahul Khair NW Pemantek. This research employed a qualitative case study approach, with data collected through in-depth interviews, participatory observation, and documentation. The data were analyzed thematically through coding and theme formulation. The results indicate that values such as honesty, responsibility, and respect for teachers are effectively internalized by students through consistent traditional teaching methods and the exemplary conduct of teachers. Senior students demonstrated a higher level of social honesty compared to new students, highlighting the importance of sustained value internalization. This study concludes that Ta’lim al-Muta’allim remains relevant as a character-building medium for students, especially in cultivating social honesty, through an integrative approach that bridges classical Islamic values and contemporary social dynamics.